Les facteurs de localisation d’un nouveau type d’établissements tertiaires : les datacentres - Henry Bakis (Netcom)
Data processing centers (or data centers) are facilities needed by the development of the Internet (websites, cloud). In particular, data centers provide hosting servers (housing) of companies or individuals for rent or roommate spaces. This paper focuses on location, energy consumption and environment related with the Internet and ICT.